Forest industry contribution to economic development of the Biobio region, Chile - P., Cristian Mardones; Gallardo A., Álvaro (Instituto de Ecología, A.C., 2012)
The aim of this study was to evaluate the effects that would have an exogenous demand shockof forestry sub-sectors (silviculture, timber, pulp and paper, and furniture) on the economic activity,wages, incomes and the environment of the Biobío Region, Chile. For this purpose, was used an EnvironmentalExtended Social Accounting Matrix for Biobío with base year 2006 which allowed simulatingimpacts of changes in final demand with a sectorial economic model. The results show that eachforestry sub-sector generates different contributions to the economic development of the Biobío region,specifically the timber industry has the highest share of GDP and is the greatest consumer of inputsfrom other sectors for their high backward linkage, silviculture is a strategic sector for its raw materialsupply, the pulp industry generates greater impact on wages and high pollutant emissions, and furnituremanufacturing generates lower pollutant emissions.